Measuring the Person-Job Fit on Perceived Productivity: A Case of Indone-sian Legislators - Kurniawan, Buyung; Marnis; Samsir; Jahrizal (Future Science / FSH-PH Publications, 2023)
Person-job fit and its relationship with technical training (Bimtek) and productivity or work performance have been widely discussed in private and public organizations but scarcely in the legislative organization. Compared to what companies have generally practiced, the mismatch between jobs and legislators' educational backgrounds and experiences is quite common. In addition, the nature of the job is often temporary and prone to rotation between commissions within legislative bodies. This study aimed to examine the impact of Bimtek on the person-job fit and productivity of legislators in Indonesia and how the experience could moderate the relationship. The research design used a quantitative method by employing a correlational approach. Of the 110 population, eighty-one Indonesian legislators were valid to be used as the respondent. Bimtek was used as the independent, person-job fit as the mediator, perceived legislation productivity was employed as the dependent, and the moderator was the experience. All hypotheses were tested using independent t-test, mediation, and moderation techniques employing Hayes PROCESS models 1, 4, and 8. The major findings showed that repeated Bimtek improved person-job fit and productivity. Legislators' experience moderated the effect of person-job fit on perceived legislation productivity. This study concludes that attempting an appropriate person-job fit and optimal legislative productivity requires sufficient technical training for legislators to perform their legislative functions. In this case, when the person-job fit increases, the new legislators have higher perceived productivity than their seniors.